The Comprehensive Test Ban Treaty: Assessing the Historical and Future Prospects in the South Asian Context - Azam, A.; Rehman, S.; Hussain, W.; Ahmad, K. M. (The Nucleus, 2018)
Catastrophic effects of nuclear bombing on Hiroshima and Nagasaki in Japan compelled the international community to take measures in order to avoid radioactive fallouts of nuclear weapons and this gave impetus to the debate of nuclear disarmament. However, major powers remained reluctant to relinquish their supremacy attained through such technological advancements. As part of these efforts, the Comprehensive Test Ban Treaty (CTBT) was finally concluded and became open for signatures in1996. CTBT is widely considered as one of the key arrangements of nuclear nonproliferation eventually leading to achieve the international objective of nuclear disarmament. However, owing to strategic calculations some major States have either not signed or not ratified the treaty. Unless the treaty is signed/ratified by the major hold out States, legally, it cannot come into force. Considering past and present trends, CTBT is likely to face the challenge of brining hold out States in its ambit. Thus, chances of CTBT coming into force seem dim in calculable future.